The Bais Yaakov Network: A Case Study for a Transnationally Sustainable Community Leadership. - Yogev, Dikla (Shofar: An Interdisciplinary Journal of Jewish Studies)
The Bais Yaakov school network represents an unusual phenomenon: a school system with strong transnational tendencies. Founded in 1917 in Poland, it developed rapidly there in the interwar period; in the 1930s, it also struck roots first in Mandate Palestine and then in North America. The Bais Yaakov network of schools, which flourishes today, tells a story of sustainability over time and space. This paper presents historical analysis and social network analysis (SNA) of the early years of the Bais Yaakov network, analyzing Hebrew press newspaper articles published between 1930 and 1948 to demonstrate how a number of key leaders in the schools' administration played a crucial role in developing the network. This network involved not only the schools themselves, but also religious advocacy and government relations. Key actors leveraged their brokering power with these larger organizations in order to expand the network in Poland and the Land of Israel. The organizational affiliations of key actors thus shed light on the place of Bais Yaakov within a larger network of community organizations: in both locations, these leaders usually held a double role as educators as well as important community figures within the broader Orthodox Jewish context. These findings suggest that the sustainability of transnational networks depends on strong leaders who are involved within the network to promote its specific global identity but who are also active and powerful in the local peripheries, amplifying network visibility within local and broader communities and maintaining beneficial connections with local governmental authorities.